Meningkatkan Hasil Belajar Teks Laporan Hasil Observasi dan Keterampilan Sosial Emosional dengan Diferensiasi Proses Siswa Kelas X SMA Negeri 21 Surabaya - Uswatun Hasanah (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This Classroom Action Research (PTK) aims to describe the improvement of learning outcomes and social emotional skills through differentiated learning process applied to the material of observation report text at SMA Negeri 21 Surabaya. This research uses a cycle design consisting of planning, observation, implementation and reflection. Data was collected through student worksheets, observation sheets, and questionnaires. The results showed an increase in learning outcomes by 17% in the first cycle, and 27% percent in the second cycle stage. Student learning outcomes are shown through the percentage of students who reach the minimum completeness criteria (KKM) which was initially 60% in the pre-cycle then increased to 77% in the second cycle, and increased to 100% in the second cycle. The results of students' socio-emotional skills are shown through observation sheets and questionnaires. This observation stage is carried out in two stages and the results are in the form of a comparison of social emotional skills before the differentiated learning approach and afterwards.